Production Performance and Nutrient Conversion Efficiency of Field Cricket (Gryllus bimaculatus) in Mass-Rearing Conditions - Jamlong Mitchaothai; Nils T. Grabowski; Rachakris Lertpatarakomol; Tassanee Trairatapiwan; Ty Chhay; Sath Keo; Achara Lukkananukool (Animals, 2022)
Currently, there is an increased interest in mass producing edible insects, e.g., field crickets (Gryllus bimaculatus), due to their market value and sustainable development. The current study aimed to measure the production performance of field crickets and to quantify the major nutrient deposition rate using a new approach for a nutrient conversion efficiency calculation for the field crickets under mass-rearing conditions. The field crickets were reared under mass-rearing conditions in the rearing crates and fed with a commercial cricket feed. Measurements for daily feed offered, final body weight, and dead cricket quantity were carried out during the feeding trial period. There were three production rounds with the same procedure for farmed cricket management. The samples of diet, adult crickets, and dead crickets were collected and then analyzed for chemical analysis of macronutrients. The production performance and nutrient conversion efficiency were calculated and then compared with applicable earlier reports for both field and house (Acheta domesticus) crickets. The production performance for the studied field crickets under mass-rearing conditions had final a body weight, an average daily gain (ADG), a feed conversion ratio (FCR), and a survival rate of 0.95 g, 23.20 mg/day, 2.94 and 88.51%, respectively. The field crickets had nutrient conversion efficiency for dry matter (DM), ash, crude protein (CP), crude fat (EE), crude fiber (CF), and nitrogen-free extract (NFE) of 13.26, 8.03, 28.95, 88.94, 34.87, and 1.85, respectively, with an adjusted nutrient conversion efficiency of 14.85, 8.99, 32.37, 99.17, 38.95, and 2.10, respectively. Thus, the production of field crickets could be performed under mass-rearing conditions, and the nutrient conversion efficiency for both adjusted and non-adjusted values could be measured.